Designing a Computer Based Test Version of a Vocabulary Test - Rizka Safriyani (Journal of English Language Teaching and Islamic Integration, 2019)
This research aims to design a Computer Based Test Version of  an  Academic  Vocabulary  Test.  This  study  is  intended  to  portray students'  capacity  in  understanding  Academic  Vocabulary.  Also,  this research also describes the student's perception of the utilization of the computer-based test.  In this study, media and material specialist were involved to confirm the content validity and product quality. Other than that,  there  are  50  learners  participated  as  the  test  taker.  Surveys  and Academic Vocabulary Test was done to resemble the data. Evaluation regarding  the  program  was  completed  concerning  material  and  the aspects of the media. The suggestion given by the expert were utilized to  enhance  the  utilization  of  the  computer-based  test.  The  validator recommends utilizing four steps; creating interface, coding, publishing, and packaging. Moreover, after the utilization of Computer Based Test, the  English  Teacher  Education  Department  students'  capacity  in understanding  the  meaning  of  Academic  Vocabulary  is  known  in  the average  level.  They  have  got  the  average  mean  score  of  53  for the vocabulary  test.  On  the other  hand,  the  result of  non-English  Teacher Education Department students' capacity in doing the test is in the low level.  They  have  got the  average  mean  score  of  35  for the  vocabulary test. Moreover, the student's opinion shows that there are 95,5% of the students provide a positive perception to the utilization of A Computer Based  Test.  They  feel  positive  because  of  the  practicality,  and  the particular effectiveness of the program to describe students' capacity in understanding Academic Vocabulary.